Corporate Governance and Capital Structure: Moderating Effect of Gender Diversity. (March 2022) - Amin, Ali; ur Rehman, Ramiz; Ali, Rizwan; Mohd Said, Ridzwana
This paper investigates the effect of corporate governance on capital structure, and moderating impact of board gender diversity on this nexus. Using a sample of 2062 firm-year observations of 226 non-financial firms listed on the Pakistan Stock Exchange (PSX) from 2008 to 2019, we have conducted multiple regression analysis, and found that larger and independent board positively affect firm leverage, whereas, the negative impact of CEO duality was observed on this relationship. Moreover, we found that gender diversity is associated with better corporate governance quality and positively impact firm's leverage. Additionally, the Generalized Method of Moments (GMM) estimation was applied for the robustness and the results obtained confirmed the main findings of the study. The study provides support for the mandatory placement of female directors on the corporate board by Code of Corporate Governance (CCG) regulations Pakistan, and needs for implementation of corporate governance mechanism in the listed firms to gain lender's confidence.